Impacts of improving water management of smallholder agriculture in the Upper Blue Nile Basin - Erkossa, Teklu; Awulachew, Seleshi Bekele; Haileslassie, Amare; Yilma, Aster Denekew (2009)
With its total area of about 200,000 square kilometers (km2), which is 20% of the country?s land mass, and accommodating 25% of the population, the Upper Blue Nile Basin (Abbay) is one of the most important river basins in Ethiopia. About 40% of agricultural products and 45% of the surface water of the country are contributed by this basin. However, the characteristic-intensive biophysical variation, rapid population growth, land degradation, climatic fluctuation and resultant low agricultural productivity and poverty are posing daunting challenges to sustainability of agricultural production systems in the basin. This calls for technological interventions that not only enhance productivity and livelihoods in the basin, but also bring about positive spillover effects on downstream water users. In this study, the farming systems in the basin have been stratified and characterized; and promising agricultural water management technologies, which may upgrade the productivity of smallholder rainfed agriculture while improving downstream water quality, have been identified. As a consequence, supplementary and full irrigation using rainwater and drainage of waterlogged soils are recognized as being among the promising agricultural water management technologies that can be easily scaled-up in the basin. The magnitude of the impacts of these technologies on the productivity of the upstream farming systems and the concomitant effects on the downstream water flow and quality are under investigation, assuming an assortment of scenarios.